Evolution of Size‐Fecundity Relationship in Medaka Fish From Different Latitudes - Shingo Fujimoto; Bayu K. A. Sumarto; Iki Murase; Daniel F. Mokodongan; Taijun Myosho; Mitsuharu Yagi; Satoshi Ansai; Jun Kitano; Satoshi Takeda; Kazunori Yamahira (Molecular Ecology, 2024)
In most fishes, the number of offspring increases with maternal body size. Although this size‐fecundity relationship often varies among species as a result of the coevolution of life‐history traits, the genetic basis of such size‐fecundity relationships remains unclear. We explored the genetic basis underlying this size‐fecundity relationship in two small medaka species, Oryzias latipes and O. sakaizumii . Our findings showed that O. sakaizumii has a higher fecundity than O. latipes , and quantitative trait locus analysis using interspecific F 2 hybrids showed that chromosome 23 is linked to the size‐fecundity relationship. In particular, the genes igf1 and lep‐b in this region are known to be associated with life‐history traits, including somatic growth, gonad maturation, and progeny numbers in various taxa. Because O. sakaizumii is distributed at higher latitudes and has a shorter spawning season than O. latipes in the wild, we propose that the relatively high fecundity observed in O. sakaizumii is an adaptation to high latitudes. We also discuss the potential ecological ramifications associated with the evolution of increased fecundity in this species.

Repositioning of centromere‐associated repeats during karyotype evolution in Oryzias fishes - Satoshi Ansai; Atsushi Toyoda; Kohta Yoshida; Jun Kitano (Molecular Ecology, 2024)
The karyotype, which is the number and shape of chromosomes, is a fundamental characteristic of all eukaryotes. Karyotypic changes play an important role in many aspects of evolutionary processes, including speciation. In organisms with monocentric chromosomes, it was previously thought that chromosome number changes were mainly caused by centric fusions and fissions, whereas chromosome shape changes, that is, changes in arm numbers, were mainly due to pericentric inversions. However, recent genomic and cytogenetic studies have revealed examples of alternative cases, such as tandem fusions and centromere repositioning, found in the karyotypic changes within and between species. Here, we employed comparative genomic approaches to investigate whether centromere repositioning occurred during karyotype evolution in medaka fishes. In the medaka family (Adrianichthyidae), the three phylogenetic groups differed substantially in their karyotypes. The Oryzias latipes species group has larger numbers of chromosome arms than the other groups, with most chromosomes being metacentric. The O. javanicus species group has similar numbers of chromosomes to the O. latipes species group, but smaller arm numbers, with most chromosomes being acrocentric. The O. celebensis species group has fewer chromosomes than the other two groups and several large metacentric chromosomes that were likely formed by chromosomal fusions. By comparing the genome assemblies of O. latipes , O. javanicus , and O. celebensis , we found that repositioning of centromere‐associated repeats might be more common than simple pericentric inversion. Our results demonstrated that centromere repositioning may play a more important role in karyotype evolution than previously appreciated.

Preface: the 10th International Charr Symposium held in Nikko, Japan - Shoichiro Yamamoto; Kentaro Morita; Satoshi Kitano (Ichthyological Research, 2024)

The past, present, and a future for native charr in Japan - Kurt D. Fausch; Kentaro Morita; Jun-ichi Tsuboi; Yoichiro Kanno; Shoichiro Yamamoto; Daisuke Kishi; Jason B. Dunham; Itsuro Koizumi; Koh Hasegawa; Mikio Inoue; Takuya Sato; Satoshi Kitano (Ichthyological Research, 2024)
Charrs ( Salvelinus ) reach their southernmost distribution in Japan, and are uniquely adapted to the short, steep streams of this island archipelago. Southern Asian Dolly Varden ( Salvelinus curilus ) occur only in Hokkaido Island, whereas white-spotted charr ( Salvelinus leucomaenis ) range to southern Honshu. Both species diverged from an ancestral lineage during the late Pliocene/early Pleistocene, when lowered sea levels created semi-enclosed water bodies in the seas of Japan and Okhotsk. Genetic analyses showed S. curilus represents the most ancient divergence from the Dolly Varden ( Salvelinus malma ) - Arctic charr ( Salvelinus alpinus ) group, and revealed five lineages of S. leucomaenis which align differently than traditional subspecies. Japanese charr display diverse and flexible life histories including anadromous fish with partial migration, and fluvial, adfluvial, and resident forms. In Hokkaido, Dolly Varden are distributed upstream and white-spotted charr downstream. They coexist in narrow sympatric zones through adaptive shifts by Dolly Varden in behavior and morphology that facilitate benthic foraging. Both species hybridize with native and nonnative salmonids, and are displaced from microhabitats and decline in abundance when rainbow trout ( Oncorhynchus mykiss ) and brown trout ( Salmo trutta ) invade. Japan streams contain over 95,000 erosion control dams which create short stream fragments (medians ~200 m). This has increased extirpation of charr populations via lower genetic diversity and stochastic and demographic factors. Tributaries provide complex rearing habitats, afford refuges from floods, and supply recruits that sustain populations in mainstem fragments and create metapopulations in connected riverscapes. Charr play central roles in linked stream-riparian food webs, and cause direct and indirect effects that cascade to streambed algae and riparian predators when linkages are disrupted by anthropogenic effects or altered by native parasites. Many charr populations are threatened by habitat fragmentation and introgression or invasion by nonnative forms, but efforts to conserve charr are growing. These include restoring connectivity among pure populations above barriers that prevent invasions, protecting tributary nurseries, and instituting angling regulations to protect headwater populations. Key steps include inventorying pure populations, identifying conservation units, selecting appropriate management based on connectivity and biotic interactions, and engaging stakeholders and youth to engender an ethic for conserving irreplaceable charr lineages.

Multiple colonizations and hybridization of a freshwater fish group on a satellite island of Sulawesi - Ixchel F. Mandagi; Bayu K. A. Sumarto; Handung Nuryadi; Daniel F. Mokodongan; Sjamsu A. Lawelle; Kawilarang W.A. Masengi; Atsushi J. Nagano; Ryo Kakioka; Jun Kitano; Satoshi Ansai; Junko Kusumi; Kazunori Yamahira (Molecular Phylogenetics and Evolution, 2023)

Genetic basis for the evolution of pelvic‐fin brooding, a new mode of reproduction, in a Sulawesian fish - Javier Montenegro; Shingo Fujimoto; Satoshi Ansai; Atsushi J. Nagano; Masahiro Sato; Yusuke Maeda; Rieko Tanaka; Kawilarang W. A. Masengi; Ryosuke Kimura; Jun Kitano; Kazunori Yamahira (Molecular Ecology, 2022)
Modes of reproduction in animals are diverse, with different modes having evolved independently in multiple lineages across a variety of taxa. However, an understanding of the genomic change driving the transition between different modes of reproduction is limited. Several ricefishes (Adrianichthyidae) on the island of Sulawesi have a unique mode of reproduction called “pelvic‐fin brooding,” wherein females carry externally fertilized eggs until hatching using their pelvic fins. Phylogenomic analysis demonstrated pelvic‐fin brooders to have evolved at least twice in two distant clades of the Adrianichthyidae. We investigated the genetic architecture of the evolution of this unique mode of reproduction. Morphological analyses and laboratory observations revealed that females of pelvic‐fin brooders have longer pelvic fins and a deeper abdominal concavity, and that they can carry an egg clutch for longer than nonbrooding adrianichthyids, suggesting that these traits play important roles in this reproductive mode. Quantitative trait locus mapping using a cross between a pelvic‐fin brooder Oryzias eversi and a nonbrooding O. dopingdopingensis reveals different traits involved in pelvic‐fin brooding to be controlled by different loci on different chromosomes. Genomic analyses of admixture detected no signatures of introgression between two lineages with pelvic‐fin brooders, indicating that introgression is unlikely to be responsible for repeated evolution of pelvic‐fin brooding. These findings suggest that multiple independent mutations may have contributed to the convergent evolution of this novel mode of reproduction.

Consideration of Genetic Structure in the Ecologically or Biologically Significant Marine Areas Criteria: A Review of Convention on Biological Diversity Regional Workshops and A Case Study of Coral Reef Conservation Planning - Takehisa Yamakita; Fumiaki Sodeyama; Akira Iguchi; Yuko F. Kitano; Kosuke M. Teshima; Akifumi Shimura; Aki Nakabayashi; Satoshi Nagai; Takashi Nakamura; Hiroaki Aizawa; Nina Yasuda (Frontiers in Marine Science, 2022)
In this study we reviewed the use of genetic information in the Ecologically or Biologically Significant Marine Areas (EBSA) of Convention on Biological Diversity (CBD). We also evaluated genetic indicators for each criterion of important marine areas. We proposed five genetic indices, mainly based on microsatellite analysis (e.g., private allele frequency and number of cryptic species), then selected EBSAs in tropical and temperate zones of Japan based on eight coral species as a case study. Finally, we compared the results with the findings from conventional species-based EBSAs. In the EBSAs genetic information was mainly used in the Northern Hemisphere, particularly in the Baltic Sea; it was rarely applied in the Southern Hemisphere and Asian regions. Although typically applied to large organisms, genetic information is used to various organisms, including benthic and bacterial communities. Genetic data are used as indicators of diversity and endemism. Genetic indices were available for all seven EBSA criteria, but only five indices of three criteria were used. Examination of important areas of corals in the temperate zone using these indices showed that the indices without genetic indicators extracted a large number of important areas in the tropics; however, the use of genetic indicators identified important locations, including in temperate zones. Comparison with conventional, mainly species-based non-genetic methods showed less than 50% agreement, although particularly important sites in marine protected areas were identified by both methods. While there is still more work to be done, such as consideration of the number of survey sites or target species, one reason is that species-based methods tend to evaluate tropical areas higher. Therefore, these genetic indices are useful for examining important regions, particularly in temperate zones; they revealed cryptic lineages, indicating that many unknown marine taxa should be considered in vulnerable marine areas. Some indicators could be extracted with additional effort, such as population size estimation, immigration, or the use of next-generation sequencing, thus guiding future studies. Because limited genetic information was available in the early stages of EBSA selection, there is a need for systematic surveys and evaluations, particularly in the Southern hemisphere, Asian region, and in small organisms.

Changes in foraging and predator avoidance behavior of Japanese dace (Pseudaspius hakonensis) to predation risk by invasive smallmouth bass (Micropterus dolomieu) in a Japanese lake - Miles I. Peterson; Satoshi Kitano (Environmental Biology of Fishes, 2021)

Resident spawning of Japanese smelt, Hypomesus nipponensis, along gravel shorelines in Lake Nojiri, Central Japan - Miles I. Peterson; Satoshi Kitano; Hideyuki Ida (Landscape and Ecological Engineering, 2021)

Genetic Structure of the Goniopora lobata and G. djiboutiensis Species Complex Is Better Explained by Oceanography Than by Morphological Characteristics - Nina Yasuda; Yuko F. Kitano; Hiroki Taninaka; Satoshi Nagai; Takuma Mezaki; Hiroshi Yamashita (Frontiers in Marine Science, 2021)
Species delimitation of closely related corals is often challenging due to high intraspecies morphological variation and phenotypic plasticity with a lack of characteristic features and scarcity of relevant molecular markers. Goniopora spp. are one such coralline group, and the species status of Goniopora lobata and Goniopora djiboutiensis , an Indian and Pacific Ocean hermatypic coral species complex, has been questioned on the basis of previous molecular and morphological analyses. To further examine the species boundaries between G. lobata and G. djiboutiensis in Japan, specimens collected from areas spanning from Ryukyu Island to temperate Japanese regions were morphologically identified based on traditional morphological descriptions. Then, the genetic structure of the G. lobata and G. djiboutiensis species complex was examined using six newly developed microsatellite markers. The majority of the collected specimens had intermediate morphologies, and a STRUCTURE analysis using the LOCPRIOR model based on typical G. lobata and G. djiboutiensis morphology indicated that there were no genetic differences between these morphologies. On the other hand, STRUCTURE analysis based on oceanographic regions revealed that there was a genetic break between the temperate and subtropical regions. This weak genetic break corresponded with the Kuroshio-associated barrier, which prevents larval transport between subtropical and temperate regions. This study confirms that the current morphological identification criteria for G. lobata and G. djiboutiensis do not match the existing genetic boundaries and thus the two should be regarded as a species complex. This study also highlighted the robustness of using a multi-locus population genetic approach, including a geographic context, to confirm the species boundaries of closely related species.

Habitat dependent predation‐competition interaction shifts of invasive smallmouth bass (Micropterus dolomieu) and resident cyprinids in the Chikuma River, Nagano Japan - Miles I. Peterson; Satoshi Kitano (Environmental Biology of Fishes, 2021)

Spawning season and nesting habitat of invasive smallmouth bass Micropterus dolomieu in the Chikuma River, Japan - Miles I. Peterson; Satoshi Kitano; Hideyuki Ida (Ichthyological Research, 2020)

Limited fine-scale larval dispersal of the threatened brooding corals Heliopora spp. as evidenced by population genetics and numerical simulation - Hiroki Taninaka; Lawrence Patrick C. Bernardo; Yuta Saito; Satoshi Nagai; Mitsuhiro Ueno; Yuko F. Kitano; Takashi Nakamura; Nina Yasuda (Conservation Genetics, 2019)

Concentration and Glycoform of Rituximab in Plasma of Patients with B Cell Non-Hodgkin’s Lymphoma - Atushi Yonezawa; Yuki Otani; Toshiyuki Kitano; Mayuko Mori; Sho Masui; Yui Isomoto; Masahiro Tsuda; Satoshi Imai; Yasuaki Ikemi; Masaya Denda; Yuki Sato; Shunsaku Nakagawa; et al. (Pharmaceutical Research, 2019)

Stream drift feeding and microhabitat competition of invasive smallmouth bass Micropterus dolomieu, native Japanese dace Tribolodon hakonensis and pale chub Opsariichthys platypus in the Nogu River, Japan - Miles I. Peterson; Satoshi Kitano (Environmental Biology of Fishes, 2019)

Temporal change in the distribution and composition of native, introduced, and hybrid charrs in northern Japan - Sho Fukui; Shannan L. May-McNally; Hirotaka Katahira; Satoshi Kitano; Itsuro Koizumi (Hydrobiologia, 2016)

Hybridization between native white-spotted charr and nonnative brook trout in the upper Sorachi River, Hokkaido, Japan - Satoshi Kitano; Satoshi Ohdachi; Itsuro Koizumi; Koh Hasegawa (Ichthyological Research, 2014)

Lake restoration by biomanipulation using piscivore and Daphnia stocking; results of the biomanipulation in Japan - Jin-Yong Ha; Mineo Saneyoshi; Ho-Dong Park; Hideshige Toda; Satoshi Kitano; Takamitsu Homma; Takehito Shiina; Yutaka Moriyama; Kwang-Hyeon Chang; Takayuki Hanazato (Limnology, 2013)

Isolation of a novel cell wall architecture mutant of rice with defective Arabidopsis COBL4 ortholog BC1 required for regulated deposition of secondary cell wall components - Kanna Sato; Ryu Suzuki; Nobuyuki Nishikubo; Sachi Takenouchi; Sachiko Ito; Yoshimi Nakano; Satoshi Nakaba; Yuzou Sano; Ryo Funada; Shinya Kajita; Hidemi Kitano; Yoshihiro Katayama (Planta, 2010)

Differences in longitudinal distribution patterns along a Honshu stream of brown trout Salmo trutta, white-spotted charr Salvelinus leucomaenis and masu salmon Oncorhynchus masou - Shoichiro Yamamoto; Satoshi Kitano; Hiroyuki Sakano; Masayuki Yagyu (Fisheries Science, 2010)

Local specialists among endangered populations of medaka, Oryzias latipes, harboring in fragmented patches - Keíichiro Iguchi; Satoshi Kitano (Environmental Biology of Fishes, 2008)

Species diversity and abundance of freshwater fishes in irrigation ditches around rice fields - Osamu Katano; Kazumi Hosoya; Kei'ichiroh Iguchi; Motoyoshi Yamaguchi; Yoshimasa Aonuma; Satoshi Kitano (Environmental Biology of Fishes, 2003)

Competitive interactions for foraging microhabitat among introduced brook charr, Salvelinus fontinalis, and native bull charr, S. confluentus, and westslope cutthroat trout, Oncorhynchus clarki lewisi, in a Montana stream - Shigeru Nakano; Satoshi Kitano; Katsuki Nakai; Kurt D. Fausch (Environmental Biology of Fishes, 1998)